Immunogenicity of Bothrops atrox (Ophidia: Viperidae) venom and its evaluation by immunoenzymatic methods - Sandoval, Gustavo A. (2011)
The immunogenicity of Bothrops atrox, “jergón”, venom was studied using ELISA and Western Blot methods, as well as cross-reactivity patterns against venoms of Bothrops brazili, Lachesis muta and Crotalus durissus. For this purpose, New Zealand white rabbits (2 kg aprox) were immunized with four 500 μg doses of B. atrox venom in a period of 90 days. Antibody production was followed using ELISA technique, and title of hiper-immune serum was determined at the end of immunization protocol. Additionally, electrophoretic patterns of venoms were analyzed by SDS-PAGE and venom reactivity against obtained serum by ELISA and Western Blot. Immunization schedule allowed a pronounced antibody production since day 20 of protocol. At the end of process, serum title was 256000, which demonstrated both efficacy and usefulness of the developed procedure. On the other hand, studied venoms showed a heterogenic protein composition according to their electrophoretic patterns, whereas cross-reactivity values of 23,7%, 4,0% and 1,8% were obtained between B. atrox venom and B. brazili, L. muta and C. durissus venoms, respectively, using immunoenzymatic methods. According to our results, this procedure constitutes an initial step for further assays directed to optimization in immunoserum production for envenoming treatment and development of kits for diagnosis and species identification of snakes.